The Glomerular Basement Membrane - Miner, Jeffrey H. (2012)
The kidney’s glomerular filtration barrier consists of two cells—podocytes and endothelial cells—and the glomerular basement membrane (GBM), a specialized extracellular matrix that lies between them. Like all basement membranes, the GBM consists mainly of laminin, type IV collagen, nidogen, and heparan sulfate proteoglycan. However, the GBM is unusually thick and contains particular members of these general protein families, including laminin-521, collagen α3α4α5(IV), and agrin. Knockout studies in mice and genetic findings in humans shows that the laminin and type IV collagen components are particularly important for GBM structure and function, as laminin or collagen IV gene mutations cause filtration defects and renal disease of varying severities, depending on the nature of the mutations. These studies suggest that the GBM plays a crucial role in establishing and maintaining the glomerular filtration barrier.